Spiradiclis spathulata (RUBIACEAE), A NEWLY RECORDED SPECIES FROM VIETNAM - Duy Hung, Vuong; Tien Quyen, Hoang (Journal of Forestry Science and Technology, 2018)
Spiradiclis spathulata was described by X. X. Chen & C. C. Huang in Guihaia (13: 3. 1993) which was based on several specimens with unknown capsules and recorded as an endemic species to China. In accordance with the collections from Cat Ba National Park, Spiradiclis spathulata was discovered as a new record for the flora of Vietnam, and the description and some figures of this species were provided. Spiradiclis spathulata is different from other Spiradiclis species in Vietnam by its short or hardly developed stems with leaves clustered at base, petiole 3 - 7 mm long, and corolla tube 17 - 25 mm long. Only a few small populations of this taxon are found in Ningming, Longzhou, and Pingxiang of Guangxi province (China) and Cat Ba National Park (Vietnam). In the Cat Ba National Park, Spiradiclis spathulata grows sparsely in evergreen broad leaved forest on the slope of limestone near Ao Ech location. The species is used for ornamental plants or ethnic medicine. According to IUCN Red list Categories and Criteria (IUCN 2012), Spiradiclis spathulata should be categorized as Vulnerable.